Synthesis of an All-Ferric Cuboidal Iron–Sulfur Cluster [FeIII4S4(SAr)4] - Moula, Golam; Matsumoto, Tsuyoshi; Miehlich, Matthias; Meyer, Karsten; Tatsumi, Kazuyuki (Angewandte Chemie International Edition, 2018)
An unprecedented, super oxidized all-ferric iron–sulfur cubanoid cluster with all terminal thiolates, Fe4S4(STbt)4 (3) [Tbt=2,4,6-trisbis(trimethylsilyl)methylphenyl], has been isolated from the reaction of the bis-thiolate complex Fe(STbt)2 (2) with elemental sulfur. This cluster 3 has been characterized by X-ray crystallography, zero-field 57Fe Mössbauer spectroscopy, cyclic voltammetry, and other relevant physico-chemical methods. Based on all the data, the electronic ground state of the cluster has been assigned to be Stot=0.
CRIS-Team Scopus Importer:2020-09-14
Keywords: high oxidation states; iron–sulfur cubane cluster; magnetism; Mössbauer spectroscopy